La representación de la mujer en la obra crónica de una muerte anunciada de Gabriel García Márquez - Gaona Tillaguango, Franklin Duman (2016)
This research focuses his intention in an important issue "REPRESENTATION OF WOMEN IN THE CHRONICLE OF A DEATH ANNOUNCED, by Gabriel García Márquez WORK." For this, the overall objective was formulated. Identify the elements or factors quantitative representation of women in the work Chronicle of a Death Foretold by Gabriel García Márquez. The methods used were: the scientific method, descriptive method, historical method, and the specific method of literary analysis that was used was the critical method based Ephraim Subero and techniques used were reading and literature review allowed to argue and investigate the various problems the study topic. In the analysis of results it is and the elements or factors that affect the representation of women, and very clear passages where women are discriminated against by the fact of not being a virgin before marriage are decoded, and thought it was a disgrace to the family and to society. Since at the time of the twentieth century with a severe prevailing ideology was paying any error or washed with blood. And so as the Vicar family, especially the two brothers Peter and Paul, met with the duty to wash the honor of killing his sister Santiago Nasar, who was slandered to be suspect of their shame suspicion. As a main result is that virginity in women was considered a fundamental aspect and essential for some men to the point that if a woman was not a virgin, could not be a marriage but the man had found lovelorn, demonstrating machismo that existed in the society of that time. In conclusion it determines that ideological factors then influenced in a negative way with regard to the representation of women at that time because the female person was a virgin at marriage and principal recommendation, it is suggested that there should be awareness in the minds of humans masculine so that there is no more discrimination as to whether or not a woman reaches virgin at marriage in order to eradicate daily violence suffered by women